2008
DOI: 10.1179/oeh.2008.14.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma Mortality in Brazil, 1980–2003

Abstract: Although asbestos causes asbestosis, lung cancer, and mesothelioma, it remains widely used in Brazil, mostly in cement-fiber products. We report the Brazilian mesothelioma mortality trend 1980-2003, using records of the national System of Mortality Information of DATASUS, including all deaths with IX International Disease Classification (ICD9) codes 163.n--pleura cancer during the period 1980-1995; and ICD10 codes c45.n--mesotheliomas and c38.4--pleura cancer for the years 1996-2003. Mesothelioma mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 14 publications
0
23
1
17
Order By: Relevance
“…This finding suggests that the peak has already passed (Price and Ware 2004). On the other hand, the peak for many South American countries (e.g., Brazil) is expected to occur in the 2010s or 2020s, due to the later ban of asbestos use (Nishikawa et al 2008; Pedra et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the peak has already passed (Price and Ware 2004). On the other hand, the peak for many South American countries (e.g., Brazil) is expected to occur in the 2010s or 2020s, due to the later ban of asbestos use (Nishikawa et al 2008; Pedra et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there is an impressive lack of studies and an underreporting of MPM cases, making it difficult to make public health decisions [6]. Pedra et al [7] studied MPM mortality in Brazil, from 1980 to 2003, and found the death frequency increased from an average of 68.4 per year in the 1980s to 110 per year in the following decade, and 157 per year in 2000–2003.…”
Section: Introductionmentioning
confidence: 99%
“…32 Pedra et al described 2,414 mesothelioma deaths in the period 1996 to 2003 in Brazil, using a combination of International Classification of Diseases 9 (ICD-9) codes 163 (malignant neoplasm of pleura) for 1980–1995 and ICD-I0 codes C45 (mesothelioma) and C38.4 (malignant neoplasm of pleura) for 1996–2003. 33 China A law with the purpose of preventing, controlling, and eliminating occupational disease hazards went into effect in China, in May 1, 2002. 34 It details all provisions for prevention and control, diagnosis, supervision and inspection, and legal responsibilities regarding occupational diseases.…”
Section: Surveillance For Ords In Low- and Middle-income Countriesmentioning
confidence: 99%
“…32 Pedra et al described 2,414 mesothelioma deaths in the period 1996 to 2003 in Brazil, using a combination of International Classification of Diseases 9 (ICD-9) codes 163 (malignant neoplasm of pleura) for 1980–1995 and ICD-I0 codes C45 (mesothelioma) and C38.4 (malignant neoplasm of pleura) for 1996–2003. 33 …”
Section: Surveillance For Ords In Low- and Middle-income Countriesmentioning
confidence: 99%